Ukraine as the Cyber Spanish Civil War - William Dixon (Ukrainian Policymaker, 2025)
The Russo-Ukrainian War, much like the Spanish Civil War, serves as a military laboratory – this time for the integration of cyber capabilities in modern state-on-state conflict. Applying Thomas Rid’s triptych of espionage, sabotage, and subversion, this article re-examines Russian and Ukrainian cyber activity from 2022– (June) 2025, drawing exclusively on open-source intelligence1. It finds that cyber espionage has evolved from long-range strategic surveillance to real-time battlefield targeting (e.g., Russia’s «Infamous Chisel»); cyber sabotage, while tactically impactful when synchronized with kinetic action, remains strategically limited (e.g., contrasted with Ukraine’s «Operation Spiderweb»); and cyber-enabled subversion is pervasive but poorly institutionalized in the West – though Ukraine’s authenticity-driven counter-disinformation campaigns demonstrate meaningful impact. Crucially, Ukrainian initiatives reveal Kyiv’s emergence as an active shaper – not merely a target – of the cyber domain. Through civil-military fusion, private-sector alignment, and crowd-sourced intelligence, Ukraine’s model has proven more responsive and integrated than Russia’s, despite the latter’s deeper technical bench. This comparative analysis underscores that organizational agility – not technical sophistication alone – is the critical determinant of cyber effectiveness. The article concludes by outlining key policy and doctrinal questions NATO allies must address to absorb the strategic lessons of this digital Spanish Civil War.